The Nigerian Fiscal Federalism and its Formula for Revenue Sharing - Ugiagbe , Imuetinyan P. J. (International Journal For Research In Business, Management And Accounting, 2017)
This is a qualitative research based on secondary sources of information. The article examines the formula that is being used for delimitation of revenue sharing in Nigeria and sometimes criticizes some of the criteria used and sometimes posits alternative cause of action that could yield a better result than what is presently possible. The manner in which revenue is shared amongst the three tiers of government that make up the federation is guided by the Nigerian constitution; therefore a meaningful discussion of the formula used for delimitation must examine the nature and character of fiscal relationship between tiers of government. It is hoped that this article would help clear the cloudy areas of revenue sharing in Nigeria and add value to the on going debate about revenue sharing in Nigeria that has become a never ending conclusion in the country.